Women, Law, and the Pursuit of Happiness in Early Harford County - Sawyer, Jeffrey K. (Harford Historical Bulletin, 1999)
Martha Griffith filed suit in 1794 against the executors of her late husband's estate. His will had left her a large, waterfront plantation on Swan Creek for the remainder of her life, but she wanted more. The suit demanded a large share of the family's working capital, specifically, livestock, supplies, farm equipment, and the slave labor force that made plantations prosperous in those times. The people and property involved in this case were for the most part members of a closely knit Harford County community, but the legal battle and its outcome had some larger implications. The decision in Griffith v. Griffith's Executors, rendered by the General Court and affirmed by the Court of Appeals, constitutes a significant piece of the legal history of early America. First, it re-established the undisputed rights of Maryland widows to a share of both the real and personal property of their deceased husbands. Second, it forced leading judges and lawyers in Maryland to undertake a deep historical and logical analysis of the authority of British legal precedents. What law would apply in cases where post-Revolutionary Maryland legislation was unclear? Third, the judgment silently affirmed that slaves in Maryland fell under the regime of personal property with respect to inheritance. The events surrounding the suit are particularly revealing of how law in action affected women with respect to inheritance and property. Despite many inequalities that affected women under the old common law in early Maryland, women had a dear legal right to own property and to use the courts of law to secure their rights, A widow's right to a reasonable share of her husband's property extended back into Anglo-Saxon times, and was one of the guarantees written into the Magna Carta. "Dower" is the old common law name for a widow's share. Customarily dower consisted of the use of and profit from one third of the deceased husband's real estate for the widow's lifetime, and one third of his personal estate after his debts were paid, But dower could also be fixed by a formal agreement.
Keywords: Maryland; Harford County; lawsuits; legal history; dower; women; property ownership; wills; plantations; real property; personal property; British legal precedents; slaves; inheritance; courts